Apoptotic Caspases Suppress Type I Interferon Production via the Cleavage of cGAS, MAVS, and IRF3 - Ning, Xiaohan; Wang, Yutao; Jing, Miao; Sha, Mengyin; Lv, Mengze; Gao, Pengfei; Zhang, Rui; Huang, Xiaojun; Feng, Ji-Ming; Jiang, Zhengfan (Molecular cell, 2019)
Viral infection triggers host defenses through pattern-recognition receptor-mediated cytokine production, inflammasome activation, and apoptosis of the infected cells. Inflammasome-activated caspases are known to cleave cyclic GMP-AMP synthase (cGAS). Here, we found that apoptotic caspases are critically involved in regulating both DNA and RNA virus-triggered host defenses, in which activated caspase-3 cleaved cGAS, MAVS, and IRF3 to prevent cytokine overproduction. Caspase-3 was exclusively required in human cells, whereas caspase-7 was involved only in murine cells to inactivate cGAS, reflecting distinct regulatory mechanisms in different species. Caspase-mediated cGAS cleavage was enhanced in the presence of dsDNA. Alternative MAVS cleavage sites were used to ensure the inactivation of this critical protein. Elevated type I IFNs were detected in caspase-3-deficient cells without any infection. Casp3−/− mice consistently showed increased resistance to viral infection and experimental autoimmune encephalomyelitis. Our results demonstrate that apoptotic caspases control innate immunity and maintain immune homeostasis against viral infection. [Display omitted] •Deficiency in apoptotic caspases leads to elevated IFN production by virus infection•Caspase-3 cleaves cGAS, MAVS, and IRF3 to keep apoptosis immunologically silent•Caspase-7 is differently involved in mouse and human cells to cleave cGAS and MAVS•MAVS is cleaved at alternative sites to ensure caspase-mediated negative regulation Ning et al. find that caspase-3 cleaves and inactivates cGAS, MAVS, and IRF3 to suppress cytokine and type I IFN production. Their findings reveal a role for apoptotic caspases in controlling antiviral innate immunity and keeping apoptosis immunologically silent.